Research / Science / Development - Stefan Hornbostel (Rat für Sozial- und Wirtschaftsdaten (RatSWD), 2009)
As in other societal realms also in research, science, and development governments and parliaments increasingly have to legitimize their actions and want to base their future activities on informed decisions. Consequently, performance measures, benchmarking, comparative analysis, "foresight studies" are increasingly asked for. Ranking, ratings and evaluations are introduced throughout the system supposedly providing on the one hand the requested transparency and at the same time acting as stimuli to improve the performance. However, to date central questions relating to the underlying methodologies and indicators used are unanswered. These questions concern the availability and appropriateness of the data, indicator construction and methodologies on the one hand, tackle issues as how to deal with effects due to disciplinary, sectoral, regional or national differences, and concern the intended and unintended effects of the instruments used. In the contribution these issues are described and discussed in more detail. In Germany so far infrastructural deficiencies e.g. the fragmentation of research groups addressing those issues prevent adequately addressing the open research questions. Behind this background the two most important tasks identified are them the development of a decentralized data collection system enabling standard definitions and the development of a competitive research infrastructure.
Keywords: 330; Science Indicators; R&D; Research Funding; Governance